PREHOSPITAL USE OF KETAMINE AND MIDAZOLAM IN AN URBAN ADVANCED PARAMEDIC PRACTITIONER SERVICE: A RETROSPECTIVE REVIEW. Issue 9 (18th August 2016) - Edwards, Tim; Shaw, Joanna; Gray, Danielle; Thomson, Neil; Faulkner, Mark
Abstract : Background: The use of ketamine and midazolam in physician-led prehospital care teams within the UK is well established. Although both agents are in use by paramedics within emergency medical systems in North America and Australasia, there is a paucity of data relating to administration by UK paramedics. Methods: A panel of clinicians utilised a standardised data extraction form to review patient report forms for all cases where an Advanced Paramedic Practitioner (APP) administered ketamine or midazolam from 1st May to 30th September 2015. Reviewers assessed indications for and appropriateness of administration, and identification and management of adverse events. Results: A total of 21 patients received ketamine for analgesia (n=20, 95%) or to facilitate rapid extrication (n=1, 5%). Pain scores were recorded in 18 patients (90%), the majority of whom experienced a reduction in pain post administration (n=17, 94%). No adverse events occurred following ketamine use. Midazolam was administered to a total of 80 cases. The most common indications for administration were maintenance of an advanced airway in patients with return of spontaneous circulation post cardiac arrest (n=37, 46%), management of acute behavioural disturbance (n=28, 35%) and prolonged seizures (n=15, 18%). Transient airway compromise occurred in 10% (n=8) of cases, all of which were managed appropriately. No other adverse events occurred. The administration of ketamine and midazolam was judged to be appropriate in all cases. Conclusions: The use of ketamine and midazolam in the context of an urban APP service with high levels of additional education, procedural experience and selective targeting to emergency calls appears safe and effective. Further prospective studies are warranted to confirm these findings.